Fracture Behavior of Engineered Cementitious Composites Concrete Under Center Point Bending Load - Al-Masraf Harith Mohammed; Al-Attar Tareq Salih; Freyyah Qais Jawad (Civil and Environmental Engineering)
Fracture behavior is an important issue to consider when analysing and designing important concrete structures. Fracture behavior is dependent on the characteristics and materials percentage in concrete. Thus, due to the application of polyvinyl alcohol fiber, this type of concrete’s structure and fracture behavior will differ from normal concrete. This investigation aims to determine some mechanical properties, in addition to the fracture parameters corresponding to low and medium compressive resistance of engineering cementitious composite concrete reinforcing by fiber for notched and un-notched beams, using size effect model techniques in contrast to conventional concrete. The outcomes illustrate an increment in modulus of rupture; both fracture energy and fracture toughness, which were incremented. At the same time, the nominal stress reduction of the notched-beam is superior to un-notched beam. Five mixes for each strength grade were cast to test fresh and hardened properties; the optimum mixture that gave the higher modulus of rupture was chosen for fracture parameters investigations. Two engineering cementitious concrete mixtures containing 1.5% and 2% polyvinyl fiber for grades M25 and M65, respectively, obtained higher modulus of rupture. Geometrically, three (75×75×400) mm, (75×150×800) mm, and (75×200×1200) mm notched-beams were investigated by applying one central point load for testing their fracture toughness, fracture energy, and characteristics length, also the influence of tensile ductility of engineering cementitious concrete. The denser interfacial transition zone of engineering cementitious concrete had the highest fracture toughness and a ductile behavior of mode of failure with a flatter fracture plane than conventional concrete. The higher fracture toughness value was observed on (M25-BC3) and (M65-BC2). Outcomes indicate that conventional concrete exhibited greater sensitivity to size effect parameter due to its poorer tensile ductility than concrete incorporating polyvinyl alcohol fiber.